DEEERS Duo an implementation of parallel database techniques to the DEEERS database - Franco, Nepomuceno II T.; Pichay, Dominador Jr. A. (2008.)
Database structures proved its worth in enterprise systems, business, organizations and other institutions as the primary way of managing and processing information. The database had evolved from simple data storage into a large-scale information machine. However, as the information domain expands, the performance level of current machines is reaching its threshold. Many come to think that the only way to solve the response time problem in request and manipulation of information in databases is to use faster but high-cost processors and employment of larger memory. With the advent of multiprocessor machines, an alternative in dealing with the problem was given. Exploiting the inherent parallel capabilities of multiprocessor machines will allow us to push the performance beyond the threshold. The objective of the DEEERS Duo project is to formulate a solution by implementing parallel database techniques to an existing database, the Department of Electrical and Electronics Engineering Resource Site (DEEERS). The project provided tools and methodologies in designing parallel database systems and aims to serve as a basis for future database implementations on large-scale basis. In the end, parallelization was able to live up to its promise of improved performance, better scalability and increased availability. The results of benchmarks showed almost 15 times increase in performance. The system was implemented up to 7 separate machines that proved its scalability. And the decreased downtime due to deployment in several machines increased its availability.
Undergraduate Student Project (B.S. CoE)--University of the Philippines, Diliman.
Keywords: Parallel processing (Electronic computers); Datbase management; Parallel database techniques